Effectiveness and impact of hepatitis B virus vaccination of children with at least one parent born in a hepatitis B virus endemic country: an early assessment. Issue 10 (12th October 2009) - Hontelez, Jan A C; Hahné, Susan; Koedijk, Femke H D; de Melker, Hester E
Abstract : Objective: To determine the effectiveness and impact of the Dutch childhood hepatitis B virus (HBV) vaccination policy targeted at children with at least one parent born in a HBV endemic country. Methods: The Dutch vaccination registration database was used to determine vaccine coverage for HBV and DTP-IPV-Hib in the target population. HBV notifications were used to estimate the impact. The HBV incidence was determined in children aged 0–4 years and born after (2003–7) and before (1990–2002) the introduction of the HBV vaccination programme. Results: HBV vaccine coverage in the target population was 89.6% (96 186/107 338) in the period 2003–5. There were 37 notified acute infections in the pre-vaccination birth cohort 1990–2002 (incidence 2.9/10 6 person-years), compared with one in the post-vaccination birth cohort 2003–7 (incidence 0.3/10 6 person-years). The incidence rate ratio for the 2003–7 birth cohort compared with the 1990-2002 birth cohort was 0.12 (95% CI 0.02 to 0.87; p=0.04). Conclusions: This paper shows that the incidence of HBV notifications in children born after the introduction of targeted childhood HBV vaccinations is lower compared with the incidence in children born before the start of this vaccination programme. Although this is consistent with a good HBV vaccine coverage, the interpretation is hampered by a change in case definition for notification in 1999. The results are of importance to policy makers in both The Netherlands and other countries that have a targeted HBV vaccination programme.